Webinar tentang Kontribusi Publik Indonesia dalam Merespons Kolonisasi Israel di Palestina: Webinar on the Contribution of the Indonesian Public in Responding to Israel's Colonization in Palestine - Aswar, Hasbi; Felani, Herman (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This article presents the results of a community service program in the form of a webinar titled The Indonesian Public's Contribution in Responding to Israel's Colonization of Palestine. The activity aimed to raise public awareness about the reality of Israel's occupation of Palestine and the communication strategies Israel uses to legitimize its actions. It also sought to educate the public on Israel's efforts to engage the Indonesian public through various media and partnerships. This program involved collaboration between lecturers from the International Relations and Communication departments of FPSB UII, who presented materials on topics such as Israel's occupation, Israel's public diplomacy strategies, global Zionist networks, and Zionist approaches through media. The webinar was conducted online over four weeks, with participants from various backgrounds, including students, lecturers, and the general public. The outcomes of this program are expected to contribute to sustaining solidarity with the Palestinian people and support efforts to end Israel's occupation in line with the 1945 Constitution.